Climate justice in India - Kashwan, Prakash (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
"The objective of the volume is to raise the primary questions of unequal effects of climate change and of climate action, with the goal of bringing these questions into ongoing scholarly and policy debates on climate change in India. It calls for moving beyond the existing debates about international versus domestic climate justice to examine the complex ways in which international and subnational policies, programs, and resource mobilizations intersect to shape the outcomes of climate action and climate justice"--
Introduction : climate justice in India / Prakash Kashwan -- Urban climate justice in India / Eric Chu and Kavya Michael -- How just and democratic is India's solar energy transition? : an analysis of state solar policies in India / Karnamadakala Rahul Sharma and Parth Bhatia -- Extractive regimes in the coal heartlands of India : difficult questions for a just energy transition / Vasudha Chhotray -- Climate justice implications of the relationship between economic inequality and carbon emissions in India / Haimanti Bhattacharya -- Climate action plans and justice in India / Arpitha Kodiveri and Rishiraj Sen -- Social mobilizations for climate action and climate justice in India / Prakash Kashwan -- Reimagining climate justice as caste justice / Srilata Sircar -- Intersectional water justice in India : at the confluence of gender, caste, and climate change / Vaishnavi Behl and Prakash Kashwan -- Realizing climate justice through agroecology and women's collective land rights / Ashlesha Khadse and Kavita Srinivasan -- Conclusion : pathways to policies and praxis of climate justice in India / Prakash Kashwan and Eric Chu.
Includes bibliographical references and index.
Keywords: Climatic changes -- Government policy -- India; Climatic changes -- Social aspects -- Inida; Environmental justice -- India; LAW / Environmental